Does sharing good news buffer fear of bad news? A daily diary study of fear of cancer recurrence in couples approaching the first mammogram post‐diagnosis. Issue 11 (23rd July 2018) - Soriano, Emily C.; Perndorfer, Christine; Otto, Amy K.; Siegel, Scott D.; Laurenceau, Jean‐Philippe
Abstract: Objective: The core of fear of cancer recurrence (FCR)—a top concern of couples after successful breast cancer (BC) treatment—is fear of death. Daily relationship processes may be instrumental in regulating FCR as triggers of existential distress are encountered. We tested the hypothesis that daily capitalization, the process of sharing good news ( capitalization attempts) to a partner perceived as responsive ( responsiveness), buffers patient and spouse FCR as they confront the first mammogram post‐diagnosis. Methods: Fifty‐seven early‐stage BC survivors and their spouses reported daily FCR, capitalization, and positivity of the disclosed event during a 3‐week diary period beginning 2 weeks before the first annual mammogram post‐diagnosis. Dyadic multilevel path models estimated within‐person effects of patient and spouse capitalization on same‐day FCR, controlling for event positivity. Results: Before the mammogram, capitalization attempts were unrelated to FCR, but for patients, responsiveness was predictive of greater same‐day FCR. After the mammogram, for both partners, attempts were predictive of greater same‐day FCR, yet responsiveness was predictive of lower FCR. Conclusions: Findings were largely inconsistent with the hypothesis that capitalization buffers existential distress. However, results revealed novel insights about daily dyadic processes that may characterize within‐person adaptation to existential threat. Potential explanations for the differential links between capitalization and FCR based on timing (before versus after threat) and capitalization component (attempts versus responsiveness) are discussed.